pH change in electroosmotic flow hysteresis - Lim, Chun Yee (2018)
Electroosmotic flow (EOF) or electro-osmosis has been shown to exhibit a hysteresis effect under displacement flow involving two solutions with different concentrations, i.e. the flow velocity for a high-concentration solution displacing a low-concentration solution is faster than the flow velocity in the reverse direction involving the same solution pair. On the basis of our recent numerical analysis, a pH change initiated at the interface between the two solutions has been hypothesized as the cause for the observed anomalies. We report the first experimental evidence of EOF hysteresis induced by a pH change in the bulk solution. pH-sensitive dye was employed to quantify the pH changes in the microchannel during EOF. The electric-field gradient across the boundary of two solutions generates an accumulation or depletion of a minority of pH-governing ions such as hydronium (H3O+) ions, thus inducing pH variations across the microchannel. When a high-concentration solution displaced a lower-concentration solution, a pH increase was observed, while the flow in the reverse direction induced a decrease in pH. This effect causes significant changes to the zeta potential and flow velocity. The experimental results show good quantitative agreement with numerical simulations. This work presents the experimental proof which validates the hypothesis of a pH change during electroomostic flow hysteresis as predicted by numerical analysis. The understanding of pH changes during EOF is crucial for accurate flow manipulation in microfluidic devices and maintenance of constant pH in biological and chemical systems under an electric field.